Dynamics of Teacher–Child Interactions in Early Childhood Education: A Sociological Paradigm Review - Vanesia Novianti; Hajerah Hajerah; Nur Magfirah Azzalfa; Fitria Nur Atsila Adiba; Musdalifah Musdalifah (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
The interaction between teachers and students is a crucial element of the learning process in Early Childhood Education (ECE). This study aims to analyze the dynamics of teacher-student interactions at PAUD Terpadu Amanah through a sociological lens, specifically focusing on the social relationships formed during learning activities. Employing a qualitative approach with a descriptive case study design, data were collected through direct observations, in-depth interviews, and documentation. The research was conducted in a class B2 setting involving 29 students and their teacher. The findings indicate that social interaction between teachers and students is highly effective, characterized by warm communication, two-way and multi-directional communication patterns, and active student engagement in learning activities. Teachers act as facilitators, guides, and positive role models who create a secure and comfortable environment. Furthermore, several factors support this positive social interaction, including adequate and complete classroom facilities, enjoyable and play-based teaching methods, and the teachers' friendly, patient, and attentive demeanor. From a sociological perspective, particularly symbolic interactionism, these interactions serve as the primary means for children to construct meaning, learn social norms, and develop their self-identity. Ultimately, the study concludes that positive social interaction fosters a comfortable learning atmosphere that significantly supports children's socio-emotional development, character formation, and overall socialization process. Continuous efforts from educators and institutions are essential to maintain these quality interactions for optimal early childhood development.